Root Canal Retreatment: A Review of The Prevalence and Factors Related to The Need for Root Canal Retreatment and Its Success Rates (Systematic Review) - Lama Talat Al-gunaid; Hamdi Hasan ALGUNAID; Nabila beutari (Cakradonya Dental Journal)
Root canal retreatment (RCR) is a critical aspect of endodontic practice, often necessitated by various factors that compromise the success of initial root canal treatments. This literature review synthesizes current research on the prevalence of RCR, associated factors leading to treatment failure, and success rates. Key factors influencing the need for retreatment include procedural errors, anatomical complexities, microbial persistence, and patient-related variables. Procedural factors, such as incomplete cleaning and shaping, inadequate obturation, and the use of outdated techniques, significantly contribute to treatment failures. Microbial persistence, particularly involving resistant strains like Enterococcus faecalis, exacerbates the challenges faced in endodontic therapy. Additionally, demographic factors, practitioner experience, and technological advancements play pivotal roles in determining treatment outcomes. Success rates for RCR vary widely, typically ranging from 70% to over 90%, influenced by the underlying causes of retreatment and the methodologies employed. Understanding these factors is essential for clinicians seeking to enhance treatment efficacy and improve patient outcomes in endodontic care. This review underscores the importance of continuous education and the adoption of innovative techniques and materials to mitigate the need for RCR and optimize success rates.